Nanocellulose synthesis from pineapple fiber and its application as nanofiller in polyvinyl alcohol-based film - Iriani, Evi Savitri; Wahyuningsih, Kendri; Sunarti, Titi Candra; Permana, Asep Wawan (Jurnal Pascapanen Pertanian, 2015)
A variety of attempts have been made to reduce the dependence on petroleum raw materials based plastics which are limited supply and difficult to degrade, so it can cause the environment problems. Polyvinyl Alcohol/PVA, one of the water-soluble polymer, has good compatibility with fillers, i.e., nanocellulose addition, so it can resulted a composite films that are environmentally friendly and the mechanical properties close to conventional plastic. The objectives of research was to know the effect of pineapple nanocellulose fibers addition on the improvement of the mechanical properties of composite films based on polyvinyl alcohol. The method for manufactured of composite films using solution casting. A simple in a one-pot process was carried out by mixing of PVA solution in various concentration of pineapple nanocellulose fibers (10% - 50%) and glycerol with 2 levels (0% and 1%). Films observations were tensile strength, elongation, crystallinity, and morphology. The results shows that the addition of nanocellulose fibers 10-40% were effective in increasing tensile strength and elongation, but the higher addition (of up to 50%) resulted in decreased elongation. The addition of glycerol on the composite film tends to lower the tensile strength and elongation. This is supported by the XRD data showed that the addition of nanocelullose was also effective to improve the crystallinity properties of the films, but the properties of crystallinity decreased after adding glycerol. The best mechanical properties of composite film produced by the treatment on nanocellulose 40% addition and without glycerol.